The Effect of Social Media on Eating Habits among Students at Jazan University - Eman Shama; Monami Mukherjee Mondal; Ogail Yousif Dawod; Nagwa E E Malik; Ammar Abdelmola; Badreldin S. R. Ahmed; Mohamed M Almaki; Nusayba Abdelrhman Alageb; Saif Elden B. Abdalla (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: To investigate changes in college students’ eating habits and their perceptions of healthier eating upon exposure to targeted advertisements and discussions on social media promoting healthier dietary practices. Methods: A cross-sectional study, utilizing a self-designed, pretested questionnaire, was conducted to assess the influence of social media on the dietary habits of college students at Jazan University in Saudi Arabia. The research encompassed a convenience sample of 300 students, ranging in age from 20 to 35 years, across various faculties. The data analysis was performed using SPSS software, which calculated frequencies for qualitative data and descriptive statistics for quantitative data. The chi-square test was employed to evaluate the relationships between categorical variables, with a P-value of less than 0.05 denoting statistical significance. Results: The study revealed a statistically significant impact of social media on the eating habits of the participants. Demographic data indicated that most participants were between the ages group of 20-35 years. In terms of daily usage, Snapchat was the platform most frequented by participants, with WhatsApp and Twitter also being popular. Again, Instagram was identified as the main source for nutritional information, followed by Twitter and Snapchat. The majority of participants depended on social media for guidance on nutrition and dietary choices. Furthermore, most participants acknowledged the influence of social media in fostering awareness about healthy eating, with many agreeing that it contributes to diminishing unhealthy eating practices. Conclusion:The research indicated that WhatsApp is the favored platform for communication and acquiring diabetes information. The participants acknowledged the contribution of social media to enhancing education, awareness, and interaction among people with diabetes, their relatives, and medical professionals. Nevertheless, considering the risks associated with social media use, health and educational organizations must ensure the information disseminated is precise and safeguards the privacy of both patients and healthcare providers.